The Influence of a Non-Physical Work Environment, Transformational Leadership, and Work Motivation as Mediating Variables on the Performance of State Civil Apparatus in the Directorate General of Metal Industry, Machinery, Transportation and Electronics: - Dini Dwi Rahmawati; Tajuddin Pogo (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyze the effect of non-physical work environments, transformational leadership, and work motivation on the performance of ASN Ditjen ILMATE. The population is all ASN employees in the ASN Directorate General of ILMATE, totaling 230 employees with a sample of 147 employees. Data analysis using the SEM-PLS technique The results of the study found evidence that, partially, the non-physical work environment and transformational leadership had an effect on ASN work motivation. Non-physical work environments, transformational leadership, and work motivation partially affect ASN performance. Non- physical work environments affect ASN performance through work motivation. Transformational leadership affects ASN performance through work motivation.